Application of the Frameworks of Intrinsic Capacity and the Hallmarks of Aging to Validate Nicotinamide Riboside as a Healthy Aging Supplement – A Meta-Analysis. (29th May 2020) - Ishtiaq, Yusrah; Nkrumah-Elie, Yasmeen; Idoine, Rebecca; Roberts, Matthew; Shao, Andrew
Abstract: Objectives: Introduction: Demonstrating the benefits of nutritional supplements on healthy aging has been challenging, as research has tended to focus on affecting disease rather than health optimization. We propose that by applying the frameworks of intrinsic capacity and the hallmarks of aging, one can more definitively demonstrate measurable benefits of a nutritional supplement. To test the validity of this approach, research previously and actively being conducted on nicotinamide riboside (NR), a precursor to the essential coenzyme nicotinamide adenine dinucleotide (NAD) was evaluated. NAD levels have been shown to decrease with age, thus NR is widely promoted as a nutritional solution for healthy aging. Objective: The goal of this analysis was to determine if the combined frameworks of intrinsic capacity and the hallmarks of aging can be used to demonstrate the benefits of NR supplementation. Methods: For preliminary assessment, a database of current and past NR research was developed. Each study was categorized as applicable to one or more of the proposed framework categories. The data were graphed by category to demonstrate historical growth in the research categories. Results: Preliminary results indicated that 30.6% of studies in the database could be categorized as including research on one or more of the hallmarks of aging; the most dominant category was that of mitochondrial dysfunction, encompassing 27 preclinical and 7 clinical studies, followed by genomic instability (17, 1), altered intercellular communication (9, 2), deregulated nutrient sensing (8, 3), stem cell exhaustion (11, 0), epigenetic alterations (2, 0), and telomere attrition (2, 0), respectively. More than half of the studies could also be categorized as relating to one or more domains of intrinsic capacity specifically Vitality (50, 2) and Locomotion (19, 4), followed by Cognition (5, 1), Sensory (4, 0), and Psychological (1, 0), (preclinical, clinical) respectively. Conclusions: NR research can be applied to multiple categories of the hallmarks of aging as well as intrinsic capacity domains, demonstrating the benefits of NR supplementation Positive results from previous and current research will further validate NR as a multidimensional healthy aging supplement. Funding Sources: None.